2022
DOI: 10.1055/s-0042-1747678
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Serum Mammaglobin as an Alternative Biomarker in the Diagnosis of Breast Tumors

Abstract: Introduction Breast cancer is the most common cancer in women in India and accounts for 14% of all cancers in women. Rise in mortality is due to lack of awareness and proper screening. Mammography and presently available serum biomarkers have low sensitivity and specificity. In our quest to identify a better biomarker, we studied mammaglobin (MAM) in patients with breast cancer and benign breast tumors. Aim To evaluate serum mammaglobin in breast cancer patients and compare it with benign breast tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Moreover, among the three markers, mammaglobin exhibits the highest specificity at 100%. 9 Three prior immunohistochemical studies have demonstrated a link between elevated levels of MAM-A protein expression and the status of ER and PR, as well as low tumor grade and absence of axillary node invasion. These findings indicate that breast cancer cases displaying increased mammaglobin-A expression are likely to be associated with less aggressive tumor characteristics.…”
Section: Human Mammaglobin a As A Diagnostic Indicatormentioning
confidence: 99%
“…Moreover, among the three markers, mammaglobin exhibits the highest specificity at 100%. 9 Three prior immunohistochemical studies have demonstrated a link between elevated levels of MAM-A protein expression and the status of ER and PR, as well as low tumor grade and absence of axillary node invasion. These findings indicate that breast cancer cases displaying increased mammaglobin-A expression are likely to be associated with less aggressive tumor characteristics.…”
Section: Human Mammaglobin a As A Diagnostic Indicatormentioning
confidence: 99%